Cultivation of landrace corn for silage in systems traditional and agroforestry - Matos, Davi Moreira; Gomes, Silas Primola; Rocha, Amanda Cardoso; França, Andrezza Araújo de; Aguiar, Maria Ivanilda de; Silva, Fred Denilson Barbosa da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
This study aimed to evaluate the production and quality of landrace corn silage produced in traditional system (TS) compared to the agroforestry system (AFS). The experimental design was completely randomized with two treatments and six replications. The silage was made in experimental silos of laboratory. Were evaluated physical and organoleptic characteristics (proportion of grains, smell, color, moisture, and particle size), agronomic parameters (stage of grain, height, number of dry leaves and dry weight of fractions of plants) and content of dry matter (DM). The height of the plants varied in the TS and AFS systems, being 15.55% higher in the TS. The stem component was the one that had the largest participation in the plant mass (49.41%), followed by the leaves (25.96%), in the TS, being higher than the values observed in the AFS. Lower values were observed for DM of the stem (23.48%), leaf (40.65%), straw (37.73%), cob (31.63%) and grains (32.28%) of plants harvested at TS, in relation to AFS, who presented values of 26.72, 59.37, 66.09, 44.30 and 43.04%, respectively, for the fractions. The levels of DM of the corn silages (whole plant) did not differ between the two systems, being 31.35% for the TS and 33.06% for the AFS, presenting an average of 32.2%. The cultivation of corn in the AFS presents less potential for production of the fiber fraction (stems and leaves) than at TS, however higher grain production was observed in AFS. The silage produced presented adequate DM level in both systems.